17β-Estradiol attenuates p38MAPK activity but not PKCα induced by angiotensin II in the brain. Issue 2 (February 2019) - Almeida-Pereira, G; Vilhena-Franco, T; Coletti, R; Cognuck, S Q; Silva, H V P; Elias, L L K; Antunes-Rodrigues, J
Abstract : 17β-Estradiol (E2) has been shown to modulate the renin–angiotensin system in hydromineral and blood pressure homeostasis mainly by attenuating angiotensin II (ANGII) actions. However, the cellular mechanisms of the interaction between E2 and angiotensin II (ANGII) and its physiological role are largely unknown. The present experiments were performed to better understand the interaction between ANGII and E2 in body fluid control in female ovariectomized (OVX) rats. The present results are the first to demonstrate that PKC/p38 MAPK signaling is involved in ANGII-induced water and sodium intake and oxytocin (OT) secretion in OVX rats. In addition, previous data from our group revealed that the ANGII-induced vasopressin (AVP) secretion requires ERK1/2 signaling. Therefore, taken together, the present observations support a novel concept that distinct intracellular ANGII signaling gives rise to distinct neurohypophyseal hormone release. Furthermore, the results show that E2 attenuates p38 MAPK phosphorylation in response to ANGII but not PKC activity in the hypothalamus and the lamina terminalis, suggesting that E2 modulates ANGII effects through the attenuation of the MAPK pathway. In conclusion, this work contributes to the further understanding of the interaction between E2 and ANGII signaling in hydromineral homeostasis, as well as it contributes to further elucidate the physiological relevance of PKC/p38 MAPK signaling on the fluid intake and neurohypophyseal release induced by ANGII.